PERTANGGUNGJAWABAN PIDANA PELAKU PEMERKOSAAN KASUS PONDOK PESANTREN DI BANDUNG JAWA BARAT - Pradani, Adhi Wahyu (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Rape is one of the fastest-growing forms of violence in many countries today, and this crime always occurs in many countries. cases of sexual harassment can occur from people not known to the victim, even those closest to him. bisexual harassment is behavior that is more sexual than something that it's into desired and results in harm to the victim or recipient of the harassment, which is predicted to destroy all the good things the victim wants in the future, causing trauma and fear that causes the victim into thinking that she it's not a person who all right again. This is because victims of sexual violence are often forced to face stigma from society and even discrimination. bisexual harassment is the first step for perpetrators to commit acts of grape. iRape cases often occur in society, especially grape that occurs against children